ATM Phosphorylates ZBP-89 at Ser202 to Potentiate p21(waf1) Induction by Butyrate - Bai, Longchuan (2007)
Histone deacetylase inhibitors (HDACi) induce growth arrest and differentiation, particularly in the colon where they are potential chemotherapeutic agents. A key mediator of HDACi action is the cyclin dependent kinase (CDK) inhibitor p21(waf1). HDACi treatment of colonic cells promotes the formation of an ATM/ZBP-89/p300 complex on p21(waf1) proximal promoter, and this multi-molecular complex plays an important role in HDACi induction of p21(waf1) expression in vitro and mucosal protection in vivo. Here we found that ZBP-89 is phosphorylated by ATM kinase in vitro and in vivo. Disruption of the ATM phosphorylation motif (202)SQ within the zinc finger domain of ZBP-89 attenuated its ability to enhance p21(waf1) activation by butyrate. Moreover, disruption of the ATM phosphorylation site abrogated the ability of ZBP-89 to potentiate butyrate induction of endogenous p21(waf1) expression. These results demonstrate that ATM phosphorylation of ZBP-89 contributes to HDACi induction of p21(waf1) gene expression.